Self-Healing Mechanism and Conductivity of the Hydrogel Flexible Sensors: A Review - Juan Zhang; Yanen Wang; Qinghua Wei; Yanmei Wang; Mingju Lei; Mingyang Li; Dinghao Li; Longyu Zhang; Yu Wu (Gels, 2021)
Sensors are devices that can capture changes in environmental parameters and convert them into electrical signals to output, which are widely used in all aspects of life. Flexible sensors, sensors made of flexible materials, not only overcome the limitations of the environment on detection devices but also expand the application of sensors in human health and biomedicine. Conductivity and flexibility are the most important parameters for flexible sensors, and hydrogels are currently considered to be an ideal matrix material due to their excellent flexibility and biocompatibility. In particular, compared with flexible sensors based on elastomers with a high modulus, the hydrogel sensor has better stretchability and can be tightly attached to the surface of objects. However, for hydrogel sensors, a poor mechanical lifetime is always an issue. To address this challenge, a self-healing hydrogel has been proposed. Currently, a large number of studies on the self-healing property have been performed, and numerous exciting results have been obtained, but there are few detailed reviews focusing on the self-healing mechanism and conductivity of hydrogel flexible sensors. This paper presents an overview of self-healing hydrogel flexible sensors, focusing on their self-healing mechanism and conductivity. Moreover, the advantages and disadvantages of different types of sensors have been summarized and discussed. Finally, the key issues and challenges for self-healing flexible sensors are also identified and discussed along with recommendations for the future.